2006
DOI: 10.1248/jhs.52.743
|View full text |Cite
|
Sign up to set email alerts
|

Neuritogenesis of Herbal Geniposide-Related Compounds in PC12h Cells

Abstract: Previously, we have reported that geniposide, a compound isolated from an extract of Gardenia fructus, has neuritogenic activity in PC12h cells, a subclone of the rat pheochromocytoma cell. In this study, we have examined the effects of seven geniposide-related compounds (S-1, 6α-hydroxygeniposide; S-2, 6β-hydroxygeniposide; S-3, 6α-methoxygeniposide; S-4, 6β-methoxygeniposide; S-5, loganin; S-6, 7-ketologanin; and S-7, syringopicroside) isolated from various medicinal herbs. The geniposide-type iridoids S-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, we have previously reported that several iridoid compounds, and their hydrolysates, have neuritogenic activity in PC12h cells [2][3][4], a subclone of a rat pheochromocytoma cell [5]. In particular, genipin, the aglycon of geniposide, potently induces neurite outgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have previously reported that several iridoid compounds, and their hydrolysates, have neuritogenic activity in PC12h cells [2][3][4], a subclone of a rat pheochromocytoma cell [5]. In particular, genipin, the aglycon of geniposide, potently induces neurite outgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…1) Furthermore, we have previously reported that several iridoid compounds, and their hydrolysates, have neuritogenic activity in PC12h cells, [2][3][4] a subclone of a rat pheochromocytoma cell. 5) Genipin, the aglycon of geniposide (gardenia jasminoides), is a particularly potent inducer of neurite outgrowth.…”
mentioning
confidence: 99%